(untitled) - Barbazette, Jean (San Francisco, CA., 2006)
The Art of Great Training Delivery is a complete guide for training success. Jean not only covers all the bases but provides nuggets of training wisdom that will last an entire career. An invaluable resource for new and veteran trainers!"
Keywords: Adult learning,Training,Người lớn học tập; Đào tạo